Effects of ACE inhibition and Angiotensin II receptor blockade on glomerular basement membrane protein excretion and charge selectivity in Type 2 diabetic patients - VELİOĞLU ÖĞÜNÇ, AYLİZ; YAVUZ, DİLEK; HAKLAR, GONCAGÜL (J R A A S LTD, 2006)
Angiotensin-converting enzyme (ACE) inhibitors may reduce urinary albumin excretion (UAE) by decreasing glomerular pressure and increasing glomerular charge selectivity through preservation of glycosaminoglycans. The effect of Angiotensin II antagonism on glomerular charge selectivity remains to be determined. The aim of this study was to compare the effects of an AT, blocker losartan and an ACE inhibitor (ACE-I) enalapril on UAE, extracellular matrix proteins, glycosaminoglycan excretion(U-GAG) and red blood cell anionic charge (RBCCh) which are the indirect markers of glomerular basement membrane anionic content in hypertensive Type 2 diabetic patients. Twenty-four patients were randomised into two groups and received either enalapril (5-20 mg/d) or losartan (50-100 mg/d). All parameters were measured at baseline and after six months of treatment. At the end of six months, systolic and diastolic blood pressures (BP), UAE rates, U-GAG excretion and RBCCh were significantly and equally reduced in both treatment groups compared with baseline. RBCCh was negatively correlated with UAE (r = -0.57, p < 0.0001) and U-GAG excretion (r = -0.57, p < 0.0001); UAE was correlated with U-GAG excretion (r = 0.58, p < 0.0001). In conclusion, enalapril and losartan treatment were equally effective in reducing BP, UAE as well as U-GAG excretion and preserving RBCCh in hypertensive Type 2 diabetic patients. ACE inhibition and AT(1)-receptor blockade may have favourable effects on preserving glomerular anionic content in hypertensive diabetic patients.
Keywords: hypertension; Type 2 diabetes mellitus; glomerular charge selectivity; angiotensin-converting enzyme inhibitors; Angiotensin II receptor blockers; CONVERTING-ENZYME-INHIBITION; HEPARAN-SULFATE PROTEOGLYCAN; SIZE-SELECTIVITY; URINARY GLYCOSAMINOGLYCAN; EXTRACELLULAR-MATRIX; IV COLLAGEN; NEPHROPATHY; MELLITUS; MICROALBUMINURIA; LOSARTAN